Gemcitabine resistance by CITED4 upregulation via the regulation of BIRC2 expression in pancreatic cancer - Eun-Jeong Jeong; Yuna Roh; Eunsun Jung; Jin-Seong Hwang; Taesang Son; Hyun Seung Ban; Tae-Su Han; Young-Kug Choo; Jang-Seong Kim (Journal of Biomedical Science)
Abstract Background Gemcitabine (GEM) is used as a first-line therapy for patients diagnosed with any stage of pancreatic cancer (PC); however, patient survival is poor because of GEM resistance. Thus, new approaches to overcome GEM resistance in PC are urgently needed. Here, we aimed to establish an in vivo drug-resistant PC model and identify genes involved in GEM resistance. We focused on one of these factors, CITED4, and elucidated its mechanisms of action in GEM resistance in PC. Methods L3.6pl, a GEM-sensitive PC cell line, was orthotopically injected into the pancreas of BALB/c nude mice to establish a GEM-resistant PC animal model. Transcriptomic data from control or GEM-resistant tumor-derived cells were analyzed. GEM resistance was evaluated using cell viability, clonogenicity, and apoptosis assays. An apoptosis array was used to identify genes downstream of CITED4. A CITED4 knockout-mediated GEM sensitivity assay was performed in an orthotopic xenograft mouse model using PANC-1 cells, which are GEM-resistant cells. Results From the RNA sequencing data of isolated GEM-resistant PC cells and The Cancer Genome Atlas dataset, 15 GEM resistance-related genes were found to be upregulated, including CITED4, the gene encoding a type of CBP/p300-interacting transactivator implicated in several cancers. CITED4 knockdown in drug-resistant cells reduced cell proliferation and migration but increased apoptosis. To identify the molecular mechanism underlying CITED4-mediated induction of GEM resistance, alterations in Baculoviral IAP Repeat Containing 2 (BIRC2) levels were observed using an apoptosis array. BIRC2 expression was downregulated following CITED4 knockdown in GEM-resistant PC cell lines. Furthermore, chromatin immunoprecipitation and promoter assays showed that BIRC2 was directly regulated by CITED4. Consistent with the CITED-knockdown experiments, silencing of BIRC2 increased the sensitivity of L3.6pl-GEM-resistant and PANC-1 cell lines to GEM. Furthermore, CITED4 knockout using the CRISPR-Cas9 system in PANC-1 cells increased the sensitivity to GEM in orthotopic mice. Moreover, elevated CITED4 and BIRC2 expression levels were associated with poorer outcomes in human PC clinical samples. Conclusions Collectively, these results indicate that CITED4 regulates GEM resistance via inhibition of apoptosis by upregulating BIRC2 expression in PC cells. Therefore, CITED4 may serve as a valuable diagnostic marker and therapeutic target for GEM-resistant PC.